Dynamic Motion of Microwave Bursts during a Solar Limb Flare - Sujin Kim; Jeongwoo Lee; Sung-Hong Park; Su-Chan Bong; Satoshi Masuda (The Astrophysical Journal)
The SOL2013-10-28T02:02:58L133C110 flare occurred on the western limb, acquiring the GOES class of X1.0, and we focus on an oscillatory phenomenon detected at 34 GHz by the Nobeyama Radioheliograph (NoRH) during this flare. The oscillation is less obvious at 17 GHz and is unseen for a hard X-ray source detected by the RHESSI. In the 94 Å images from the Atmospheric Imaging Assembly on board the Solar Dynamics Observatory, we traced the evolution of the extreme ultraviolet (EUV) images capturing an eruption around 01:58 UT over the location of the RHESSI 50–100 keV source. We located the microwave emitting loop inferred from the 17/34 GHz maps within the complex EUV loop systems, and performed a model calculation of the dynamic evolution of the microwave brightness, including the radiative transfer in a magnetically asymmetric loop and evolving nonthermal electrons. The results demonstrate that a quasiperiodic injection of energetic electrons at a fixed spatial point is sufficient to reproduce such an oscillatory motion, without an actual shift of the nonthermal electron injection point, and that the magnetic environment required for the microwave loop model is consistent with the observed EUV activities related to the overall reconnection geometry.